Dexamethasone Provides Effective Immunosuppression for Improved Survival of Retinal Organoids after Epiretinal Transplantation - Bikun Xian; Ziming Luo; Kaijing Li; Kang Li; Mingjun Tang; Runcai Yang; Shoutao Lu; Haijun Zhang; Jian Ge (Stem Cells International)
We investigated the efficacy of the immunosuppressants rapamycin (RAP) and dexamethasone (DEX) in improving the survival of retinal organoids after epiretinal transplantation. We first compared the immunosuppressive abilities of DEX and RAP in activated microglia in an in vitro setting. Following this, we used immunofluorescence, real-time polymerase chain reaction, and flow cytometry to investigate the effects of DEX and RAP on cells in the retinal organoids. Retinal organoids were then seeded onto poly(lactic-co-glycolic) acid (PLGA) scaffolds and implanted into rhesus monkey eyes (including a healthy individual and three monkeys with chronic ocular hypertension (OHT) induction) and subjected to different post-operative immunosuppressant treatments; 8 weeks after the experiment, histological examinations were carried out to assess the success of the different treatments. Our in vitro experiments indicated that both DEX and RAP treatments were equally effective in suppressing microglial activity. Although both immunosuppressants altered the morphologies of cells in the retinal organoids and caused a slight decrease in the differentiation of cells into retinal ganglion cells, the organoid cells retained their capacity to grow and differentiate into retinal tissues. Our in vivo experiments indicate that the retinal organoid can survive and differentiate into retinal tissues in a healthy rhesus monkey eye without immunosuppressive treatment. However, the survival and differentiation of these organoids in OHT eyes was successful only with the DEX treatment. RAP treatment was ineffective in preventing immunological rejection, and the retinal organoid failed to survive until the end of 8 weeks. DEX is likely a promising immunosuppressant to enhance the survival of epiretinal implants.